Sheila Rae, the brave - Henkes, Kevin (New York : Greenwillow Books, 1987)
When brave Sheila Rae, who usually looks out for her sister Louise, becomes lost and scared one day, Louise comes to the rescue.
b
b
Keywords: Sisters -- Fiction; Courage -- Fiction; Mice -- Fiction